Two lysozymes are involved in the larva-to-pupa transition and the antibacterial immunity of Lasioderma serricorne (coleoptera: Anobiidae). (January 2021) - Yan, Yi; Yang, Hong; Xu, Kang-kang; Hu, Da-Ming; Yang, Wen-jia
Abstract: Lysozymes play important roles in the innate immune response against pathogen infections of insects. In this study, i-type and c-type lysozymes ( LsLysI and LsLysC ) were identified from the cigarette beetle, Lasioderma serricorne . Both genes were highly expressed in late larvae and pupae, especially in the fat body and integument. The expression of LsLysI and LsLysC was induced by 20-hydroxyecdysone. The expression levels of both LsLys genes were significantly upregulated after peptidoglycan (PGN) exposure and gram-positive bacterium Staphylococcus aureus infections. RNA interference (RNAi)-mediated knockdown of LsLysI or/and LsLysC in 5th instar larvae reduced lysozyme levels and disrupted the larva-to-pupa molt. Knockdown of LsLysI or LsLysC alone, and co-suppression of both genes, increased larval mortality by 13.3%, 21.1%, and 43.3% after S . aureus infection. The results demonstrated that LsLysI and LsLysC play key roles in a successful larva-to-pupa transition and in the innate immune response of L . serricorne . Highlights: One i-type and c-type lysozymes were identified in the cigarette beetle Lasioderma serricorne. The expression patterns of these two type lysozymes were similar. Knockdown of LsLysI or LsLysC disrupted the larva-to-pupa transition. Inhibition of LsLysI or LsLysC increased the mortality of larvae exposed to Staphylococcus aureus.